Transparently Hierarchical: Punctuation in the Townshend Family Recipe Book - Thaisen, Jacob (International Journal of English Studies, 2020)
The three scribes of a mid-seventeenth-century collection of medical recipes resemble each other in how they have punctuated the recipes, although they did not work simultaneously. They draw on similar repertoires of marks and they mark similar functions, but they do not use the same marks for the same functions. The principal function is the global one of indicating where the constitutive elements of the recipes begin and end. This function of indicating a text’s structural hierarchy goes back centuries and can seem old-fashioned for an Early Modern English manuscript produced when grammarians had started to discuss whether punctuation should mark syntactic units. A key observation is that recipes stand out among text-types by having a fixed, transparently hierarchical structure. This feature of them facilitates the researcher’s appreciation of how the punctuation functions and dismisses any impression of the scribes having deployed the marks haphazardly.